1982
DOI: 10.1016/0378-5173(82)90122-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ionization and ion-pair formation on lipophilicity of some 4-hydroxycoumarin derivatives in the octanol-water system

Abstract: SummaryThe pH-dependent distribution of weak acids in the octanol-water system was investigated. For a series of six 4-hydroxycoumarins, substituted at position 3, the apparent partition coefficient or the distribution coefficient, Per,,,, was measured in the pH range 1-i 1. The log Parr, -pH profiles obtained are in complete agreement with the theory. At high pH the value of Pap,, is independent of pH, but dependent on the concentration of counterions (Na+ in this study) in the aqueous phase; in other words i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…The solubility, pK a and log D 7.4 values determined experimentally for monobasic acid 4-HC were in accord with the literature data (28). In the pH region where pH >> pK a (or pH > pK a + 1.5), the equation log D = log P -pH + pK a holds and can be used to estimate the partition coefficient of the undissociated monobasic acid (log P) when the pK a value is al-ready known.…”
Section: Physicochemical Properties Of Synthesized Hydrazinyldiene-chsupporting
confidence: 74%
See 1 more Smart Citation
“…The solubility, pK a and log D 7.4 values determined experimentally for monobasic acid 4-HC were in accord with the literature data (28). In the pH region where pH >> pK a (or pH > pK a + 1.5), the equation log D = log P -pH + pK a holds and can be used to estimate the partition coefficient of the undissociated monobasic acid (log P) when the pK a value is al-ready known.…”
Section: Physicochemical Properties Of Synthesized Hydrazinyldiene-chsupporting
confidence: 74%
“…In the pH region where pH >> pK a (or pH > pK a + 1.5), the equation log D = log P -pH + pK a holds and can be used to estimate the partition coefficient of the undissociated monobasic acid (log P) when the pK a value is al-ready known. Log P of 4-HC thus obtained was 2.63, which is fairly close to the value of 2.37 determined by van der Giessen and Janssen (28). Experimentally determined distribution coefficients (log D 7.4exp ) of the synthesized compounds ranged between -0.096 (1c) and 0.602 (1e).…”
Section: Physicochemical Properties Of Synthesized Hydrazinyldiene-chsupporting
confidence: 64%
“…In a previous communication from our laboratory (van der Giesen and Janssen, 1982) it was reported that the apparent partition coefficient of warfarin at pH 10.0 (warfarin has a pK of 5.0 and is completely dissociated under those conditions) was increased by the presence of Nat ions. A linear relationship between the logarithm of the apparent partition coefficient Kapp and the negative logarithm of the sodium ion concentration pNa was observed.…”
mentioning
confidence: 99%